2012
DOI: 10.5152/akd.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of mean platelet volume in young patients with non-ST-segment elevation acute coronary syndromes: a retrospective observational study

Abstract: Predictive value of mean platelet volume in young patients with non-ST-segment elevation acute coronary syndromes: a retrospective observational study ST-yükselmesiz ABSTRACTObjective: Platelets play an important role in both initiation and propagation of acute coronary syndromes. We sought to evaluate the predictive value of mean platelet volume (MPV) in young patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS).Methods: This is a retrospective observational study; evaluating the MPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Recently, clearly known that increased MPV is shown more reactive platelets. We also known that increased in MPV is closely correlated with thrombosis and to reflect thrombosis burden in different condition and increase in MPV has been identified as an independent risk factor of recurrent vascular events [9][10][11]16 . Previous studies showed that there is the hypercoagulable/prothrombotic state in APE, which is also important in development of thrombosis 17 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, clearly known that increased MPV is shown more reactive platelets. We also known that increased in MPV is closely correlated with thrombosis and to reflect thrombosis burden in different condition and increase in MPV has been identified as an independent risk factor of recurrent vascular events [9][10][11]16 . Previous studies showed that there is the hypercoagulable/prothrombotic state in APE, which is also important in development of thrombosis 17 .…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that MPV is a marker of platelet function and is positively associated with indicators of platelet activity [5][6][7]9 . Recently, clearly known that increased MPV is shown more reactive platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasoactive mediators secreted by the platelets may contribute to inflammation and the process of atherogenesis. Increased risk of acute coronary syndrome in patients with high MPV may be explained by increased platelet activity, inflammation, and platelet aggregation [10] . MPV has been found to be more closely related to platelet function than to platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MPV is another recent hematologic parameter being extensively investigated. A number of studies have demonstrated that higher MPV values are associated with poorer long-term outcome in patients presented with ACS [13][14][15]. Therefore, increased levels of both WBC and MPV levels were shown to be associated with adverse CV outcomes; the proposed novel marker, WMR, would most likely blunt the predictive power of these parameters, as a result of dividing WBC by MPV.…”
mentioning
confidence: 99%